2021
DOI: 10.1016/j.afjem.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Results from the implementation of the World Health Organization Basic Emergency Care Course in Lagos, Nigeria

Abstract: Background The emergency care of time-sensitive injuries and illnesses is increasingly recognized as an essential component of effective health care systems. However, many low- and middle-income countries (LMICs) lack healthcare providers formally trained in the care of emergency conditions. The Disease Control Priorities 3 project estimates that effective emergency care systems could avert up to half of all premature deaths in LMICs. Nigeria, a lower-middle income country of nearly 200 million pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 9 publications
3
20
0
Order By: Relevance
“…Low response rates in surveys of healthcare professionals has been well documented in the literature [15]. In addition, even lower response rates amongst physicians have also been noted in LMICs consistent with the response rate in the study [16][17][18]. However, research has suggested that nonresponse bias is less of a concern amongst the physician population [15,[19][20][21].…”
Section: Limitationssupporting
confidence: 69%
See 2 more Smart Citations
“…Low response rates in surveys of healthcare professionals has been well documented in the literature [15]. In addition, even lower response rates amongst physicians have also been noted in LMICs consistent with the response rate in the study [16][17][18]. However, research has suggested that nonresponse bias is less of a concern amongst the physician population [15,[19][20][21].…”
Section: Limitationssupporting
confidence: 69%
“…For example, a recently published 2017 quasi-experimental study based in Tanzania and Uganda identified that participants of a 5-day BEC training shows a significant increase in emergency care knowledge and confidence at all four study sites [20]. Similarly in Nigeria, post-BEC test scores showed a significant improvement as compared to pre-course (73% vs. 86.5%, p < 0.001) [17].…”
Section: Plos Onementioning
confidence: 98%
See 1 more Smart Citation
“…For each skill, we reported the number and proportion of participants responding “very comfortable”. This outcome was selected for consistency with prior studies [ 10 , 12 , 20 ]. For the COVID-19 assessment, a group of content experts developed and refined ten questions on experience and comfort treating COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…The World Health Organization (WHO) and International Committee of the Red Cross’s Basic Emergency Care Course (BEC) is an open-access five-day course for front-line emergency care providers in resource-limited settings [ 8 ] that has been implemented in multiple countries including Ethiopia [ 9 ], Zambia [ 10 ], Uganda [ 11 ], Tanzania [ 11 ], and Nigeria [ 12 ]. The BEC employs lectures and hands-on skill-based exercises to train providers in the assessment and management of emergency conditions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%